A Simple Metal-Free Cyclization for the Synthesis of 4-Methylene-3-Substituted Quinazolinone and Quinazolinthione Derivatives: Experiment and Theory - Yan, Huihui; Xiao, Xu-Qiong; Hider, Robert C.; Ma, Yongmin (Frontiers in Chemistry, 2019)
A new series of 3-substituted 4-methylene-quinazolinthiones and 4-methylene-quinazolinones were synthesized in moderate to excellent yield through a simple reaction of 2-aminoacetophenones with isocyanates or isothiocyanates. The reaction shows good tolerance of many important functional groups in the presence of air and water under metal-free conditions. Only water is produced as a coproduct, rendering this “green” methodology a highly versatile and eco-friendly alternative to the existing methods for the construction of the quinazolinone/quinazolinthione framework. We have interpreted the reaction mechanism by use of quantum chemical calculations on the basis of state-of-the-art computational methods SMD-B3LYP-D3(BJ)/BS1//B3LYP/BS1.